La topographie légendaire des itinéraires de la navette - Xavière Lanéelle (Conserveries Mémorielles)
The speed acceleration has made a daily route place of residence / place of work of over two hundred kilometers possible for the TGV-commuters. The commuter, the train and the route have been the object of a myth to serve a commercial policy as well as a development of the served cities.But the legend settled down only because it is one of the anthropological foundations and because the myth allows to combine incompatible elements, here the combination of the requirements of contemporary modernity and a more traditional life of provincial rooting.One of the aspects of the myth is that the TGV is a sterile environment and the countryside it goes through, a "black hole". Is it really the case ? Social practices and memory reinvest places and sometimes invent them. That's how a fabled topography is being built which sometimes confirms this mythical apprehension of the route, sometimes invents it.